O fardamento escolar e suas relações de poder na escola - Cavalcanti, Ana Carolina Protasio (2024)
School uniforms have been present in our society for a long time. Initially, it had the purpose of identifying students and standardizing clothing, but other meanings became attached to it over the years. Thus, based on studies on the constitution of the school, fashion and school uniforms and the taming of bodies, this work aims to understand in what ways the uniform is used, both within and outside the school space, in taming of bodies. For this purpose, we conducted a bibliographic research to find references that align with our theme and to utilize in our analysis and we also relied on a case study to examine how these issues appear in the images analyzed in the discussion of this work. The imagery study and our analyses allowed us to verify that the school uniform not only has an aesthetic appeal but also seeks to discipline bodies and standardize them according to the dominant norms of our social structure. Therefore, we hope that this study contributes to understanding the influences caused by the use of school uniforms, as well as how social standards and norms are reproduced through them.